The effect of sodium ascorbate 35% combination of surfactant 0,4% application frequency and different intracoronal bleaching on composite resin microleakage: an experimental study - Elitasari, Denti; Nugraheni, Tunjung; Untara, Tri Endra (Fakultas Kedokteran Gigi Universitas Padjadjaran, 2026)
Introduction: Bleaching with hydrogen peroxide produces free radicals in dentin which can interfere with the penetration of adhesive materials and the polymerization process of composite resin, thereby increasing the occurrence of microleakage. In cases of severe discoloration, bleaching can be repeated more than once to maximize the color change. Repeated bleaching will increase free radical residues, so more antioxidants are needed. The purpose of this study was to examine the effect of the frequency of application of sodium ascorbate 35% combined with surfactant 0,4% at different intra coronal bleaching frequencies on microleakage of composite resin. Methods: The research sample consisted of 30 premolars prepared with class I cavities with a diameter of 3 mm and a depth of 6 mm. The samples were divided into 2 groups, group I was bleached twice while group II was bleached three times, after bleaching each group was divided into 3 subgroups, group A was incubated for 7 days then filled with composite resin, group B was applied with sodium ascorbate 35% combined with surfactant 0,4% twice then filled with composite resin, group C was applied with sodium ascorbate 35% combined with surfactant 0,4% three times then filled with composite resin. All samples were observed for microleakage using a scanning electron microscope (SEM). Results: The results of the two-way ANOVA test showed that there was a significant effect of the frequency of sodium ascorbate application and the frequency of bleaching on microleakage with a value of p=0.001 (p<0.05) and there was an interaction between the frequency of sodium ascorbate 35% combined with 0,4% surfactant application and the frequency of bleaching on microleakage of composite resin. Conclusion: The frequency of application of sodium ascorbate 35% combined with surfactant 0,4% and different intracoronal bleaching has an effect on the level of composite resin microleakage.Efek frekuensi aplikasi sodium askorbat 35% kombinasi surfaktan 0,4% dan bleaching intrakoronal yang berbeda terhadap kebocoran mikro resin komposit: studi eksperimenPendahuluan: Bleaching dengan hidrogen peroksida menghasilkan radikal bebas pada dentin yang dapat mengganggu penetrasi bahan adhesif dan proses polimerisasi resin komposit sehingga meningkatkan terjadinya kebocoran mikro. Pada kasus perubahan warna yang berat, bleaching dapat diulang sebanyak lebih dari satu kali untuk memaksimalkan perubahan warna. Bleaching yang dilakukan secara berulang akan meningkatkan residu radikal bebas, sehingga dibutuhkan antioksidan yang lebih banyak. Tujuan penelitian ini untuk menguji pengaruh frekuensi aplikasi sodium askorbat 35% kombinasi surfaktan 0,4% pada frekuensi bleaching intrakoronal yang berbeda terhadap kebocoran mikro resin komposit. Metode: Sampel penelitian berupa 30 premolar yang di preparasi kavitas kelas I dengan diameter 3 mm kedalaman 6 mm. Sampel dibagi menjadi 2 kelompok, kelompok I dilakukan bleaching dua kali sedangkan kelompok II dilakukan bleaching tiga kali, pasca dilakukan bleaching, masing-masing kelompok dibagi menjadi 3 sub kelompok yaitu kelompok A di inkubasi selama 7 hari kemudian di tumpat resin komposit, kelompok B diaplikasi sodium askorbat 35% kombinasi surfaktan 0,4% dua kali kemudian di tumpat resin komposit, kelompok C diaplikasi sodium askorbat 35% kombinasi surfaktan 0,4% tiga kali kemudian di tumpat resin komposit. Seluruh sampel dilakukan pengamatan kebocoran mikro dengan menggunakan scanning electron microscope (SEM). Hasil: Hasil uji ANAVA dua jalur menunjukkan bahwa terdapat pengaruh yang signifikan frekuensi aplikasi sodium askorbat dan frekuensi bleaching terhadap kebocoran mikro dengan nilai p=0,001 (p<0,05) dan terdapat interaksi antara frekuensi aplikasi sodium askorbat 35% kombinasi surfaktan 0,4% dan frekuensi bleaching terhadap kebocoran mikro resin komposit. Simpulan: Frekuensi aplikasi sodium askorbat 35% kombinasi surfaktan 0,4% dan bleaching intrakoronal yang berbeda berpengaruh terhadap tingkat kebocoran mikro resin komposit.